fMRI Resting-State Connectivity between Language and Nonlanguage Areas as Defined by Intraoperative Electrocortical Stimulation in Low-Grade Glioma Patients - van Lieshout, Jasper; Debaene, Wouter; Rapp, Marion; Noordmans, Herke Jan; Rutten, Geert-Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background and Objectives It remains to be determined whether noninvasive functional imaging techniques can rival the clinical potential of direct electrocortical stimulation (DES). In this study, we compared the results of resting-state functional magnetic resonance imaging (rs-fMRI) to those of DES for language mapping. Our goals were twofold: (1) to replicate a previous study that demonstrated that resting-state connectivity (RSC) was significantly larger between positive DES language sites than between negative DES language sites and (2) to compare the spatial resolution of rs-fMRI to that of DES.Methods We conducted a retrospective study of nine low-grade glioma patients. Language sites were identified by intraoperative DES. We compared RSC values between and within groups of DES-positive and DES-negative regions of interest (ROIs). Both close-negative sites (i.e., DES-negative sites <1 cm apart from and on the same gyrus as DES-positive sites) and far-negative sites (i.e., purely randomly chosen sites not in the vicinity of the tumor or of the DES-positive sites but on the same lobe) were included. Receiver operating characteristics were used to quantify comparisons.Results Functional connectivity between all positive language sites was on average significantly higher than between all close-negative sites and between all far-negative sites. The functional connectivity between the positive language ROIs and their respective close-negative control sites was not smaller than between all positive language sites.Conclusion rs-fMRI likely reflects similar neural information as detected with DES, but in its current form does not reach the spatial resolution of DES.
Keywords: resting-state fMRI; direct electrocortical stimulation; language; glioma